2003
DOI: 10.1063/1.1535747
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecule formation in low density CF4 plasmas: The influence of H2

Abstract: High molecular weight fluorocarbon species are regarded as important contributors to the nucleation of films and particulates in fluorocarbon plasmas. The chemical reaction mechanisms by which fluorocarbon macromolecules form within a plasma are generally unknown. To elucidate these mechanisms, experiments were conducted in a rf capacitively coupled discharge in a Gaseous Electronics Conference reference cell. The relationships between macromolecule growth and plasma pressure, power, flow rate, and the fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…Figure 2 shows that the fluorine content introduced by CF 4 ICP is more than that introduced by CF 4 CCP at a fixed power of 200 W and the same treatment time, and both F contents obtained by the two processing techniques reach saturation when the treatment time is equal to or longer than 10 min. This corresponds to the results that CF 4 plasma fluorination and ablation or etching exist simultaneously and compete on the surface of the treated polymer, and this competition is closely related to the treatment power and time 19–21. Figure 3 shows that the ratio of [FC]/[FSi] for the SIR sample treated by CF 4 CCP is less than 0.25, and it decreases slightly with the increase of treatment time from 2 to 5 min, and then remains in the same state in spite of the increase of treatment time.…”
Section: Resultssupporting
confidence: 73%
“…Figure 2 shows that the fluorine content introduced by CF 4 ICP is more than that introduced by CF 4 CCP at a fixed power of 200 W and the same treatment time, and both F contents obtained by the two processing techniques reach saturation when the treatment time is equal to or longer than 10 min. This corresponds to the results that CF 4 plasma fluorination and ablation or etching exist simultaneously and compete on the surface of the treated polymer, and this competition is closely related to the treatment power and time 19–21. Figure 3 shows that the ratio of [FC]/[FSi] for the SIR sample treated by CF 4 CCP is less than 0.25, and it decreases slightly with the increase of treatment time from 2 to 5 min, and then remains in the same state in spite of the increase of treatment time.…”
Section: Resultssupporting
confidence: 73%
“…However, the BDDF-plasma electrode contained a mixture of CF (4.32%), CF 2 (2.81%), and –CF 3 (1.17%) groups (Figure S1b and Table ) which yielded a CF:CF 2 :CF 3 molar ratio of 3.7:2.4:1 (Table ). These results indicated that the attachment of free radicals (e.g., CF • , CF 2 • , CF 3 • , and F • ) occurred during the CF 4 plasma treatment. , The BDDF-PFOA electrode showed 15.2% surficial oxygen content, which may have formed during the synthesis process (i.e., electrochemical oxidation of formic acid and water) and indicates the surface was not completely fluorinated . The CF:CF 2 :CF 3 ratio for the BDDF-PFOA electrode was 0:2.6:1 (Table ).…”
Section: Resultsmentioning
confidence: 91%
“…All other rates were orders of magnitude lower and not of relevance for the plasma chemical model. Rates of fragmentation by binary electron collisions with other molecules were calculated by applying the electron density to the formulas for the rates given in the literature,11, 42 using an average mean electron energy of $\langle \varepsilon \rangle = 5.9\;{\rm eV}$ . The simulated densities of CF and CF 2 , based on these process rates and the reaction data in Table 1–3, were $n_{{\rm CF}} = 3 \times 10^{12} \,{\rm cm}^{{-} {\rm 3}} $ and $n_{{\rm CF}_{{\rm 2}} } = 1 \times 10^{13} \,{\rm cm}^{{-} {\rm 3}} $ during the plasma glow (converged data, 10th simulated plasma pulse).…”
Section: Resultsmentioning
confidence: 99%